Apple stem grooving virus naturally infects Himalayan wild cherry (Prunuscerasoides D. Don). Issue 2 (28th October 2015) - Bhardwaj, P.; Ram, R.; Zaidi, A. A.; Hallan, V.
Summary: Himalayan wild cherry ( Prunus cerasoides ), widely distributed in the Himalayas, was found to exhibit severe virus‐like symptoms (chlorotic spots, chlorosis along the margins of the leaf and necrotic spots). Of 47 symptomatic and asymptomatic leaf samples tested through DAS‐ELISA, dot‐blot hybridization and RT‐PCR, only three were found to be positive for Apple stem grooving virus (ASGV) infection. The complete coat protein gene from all the three positive samples was molecularly characterized and sequencing of the amplicons confirmed presence of the virus. The three characterized isolates of Himalayan wild cherry (HWC‐15, HWC‐16 and HWC‐47) grouped with the ASGV apple isolates from India, Brazil and China. Of the three, two isolates (HWC‐15 and HWC‐47) shared around 100% sequence identity among themselves while 96.2% with the third isolate (HWC‐16) (both at nucleotide and amino acid level), respectively. While they all shared an overall identity of around 92.8–99% at (aa) and 86.5–99.5% at (nt) with rest of the isolates from different hosts and geographical locations. Experimental host range of the variant HWC‐16 isolate identified C. amaranticolor, C. sativus, C. quinoa, P. vulgaris, N. benthamiana and N. glutinosa as positives for the ASGV isolate‐inducing epinasty, symptomless carrier, chlorotic spots, interveinal chlorosis, chlorotic spots and chlorotic patch. To the best of our knowledge, this is a first report of natural infection of ASGV on Himalayan wild cherry.